Factors Contributing to Academic Stress among Islamic Education Masters Students in the Class of 2024 at Sultan Agung Islamic University: English - Irfan, Alif; Choeroni; Muchtar, Asmaji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study examines the elements that contribute to academic stress among master's students in Islamic Education from the class of 2024 at Sultan Agung Islamic University. A quantitative study approach was utilised, involving a sample of 100 students, with data obtained using a questionnaire. The findings indicate that both internal and external variables substantially influence academic stress, albeit in differing degrees. Internally, self-confidence and time management skills were seen as critical variables, with 57% of respondents reporting that insufficient self-confidence exacerbated their academic stress, while 60% admitted that inadequate time management skills intensified academic strain. Nonetheless, learning motivation was shown to exert a little influence, as 79% of participants did not see poor motivation as a principal factor contributing to stress. Concerning external influences, social pressures were identified as the predominant driver, with 60% of respondents acknowledging that social expectations significantly influenced their academic stress. Conversely, 77% and 94% of respondents did not see physical and psychological environmental circumstances, together with familial pressure, as major factors. Most kids did not find high academic standards onerous, however others felt burdened. In conclusion, self-confidence and time management were recognised as the most impactful internal elements, but social expectations were seen as the most significant external component. This study's findings offer significant insights for educational institutions to formulate more effective measures to alleviate academic stress by addressing internal and external causes